Learning the way: Teaching and learning with and for youth from refugee backgrounds on Prince Edward Island - MacNevin, Joanne (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
This article presents one component of a qualitative study that explored teaching and learning with and for youth from refugee backgrounds in Prince Edward Island (PEI) intermediate and high schools. Specifically, this article presents data and discussion regarding some of the challenges and professional development needs of teachers working with refugee youth. Findings from this study confirm that improvements are needed in services available to these students such as teacher training, resources, and school inclusive practices. Teachers also expressed the need for ongoing professional development related to areas such as teaching basic reading and working with students who have experienced trauma. Practical implications for policy and practice are discussed in relation to current research literature. Keywords: refugee youth, teaching, teacher training, language acquisition, inclusion